Root system and root and stem base organic reserves of pasture Tanzania grass fertilizer with nitrogen under grazing - Soares Filho, Cecilio Viega [UNESP]; Cecato, Ulysses; Ribeiro, Ossival Lolato; Cruz Roma, Claudio Fabricio da; Jobim, Cloves Cabrera; Beloni, Tatiane; Venturoli Perri, Silvia Helena [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
The goal of this study was to evaluate the concentrations of non-structural carbohydrate (NSC) and of total nitrogen (N), as well as, to evaluate the root system in Tanzania-grass pastures fertilized with doses of urea in fall, spring and summer. The experiment was conducted at the Experimental Farm of Iguatemi, Maringa, Parana, Brazil, from March 2007 to March 2008. The experimental design was complete random blocks with subplots and four repetitions. The plots showed doses of N (50, 100 e 150 kg ha(-1) of N) plus the control (no N fertilization), and the subplots the season of the year. Root samples were taken at depths of 0-10, 10-20 and 20-40 cm. Root biomass showed a trend for mass accumulation up to a dosage of 100 kg ha(-1) for all seasons evaluated. Also, about 80% of the root system of Tanzaniagrass plants was found on the 0-10 cm layer for all dosages of N. Nitrogen fertilizer above 100 kg ha(-1) may foster fast forage plant growth reducing its NSC root storage capacity although favoring NSC and total N storage at stem base. NSC and total N concentrations were highest in fall, demonstrating that its usage is greater in spring due to the weather conditions being favorable to plant growth. In the regrowth, the largest reserve of total N was at the 0-10 cm root layer and the largest NSC reserve is at stem base.
Keywords: Panicum maximum; non-structural carbohydrates; total nitrogen; root biomass